THE IMPACT OF SOCIAL MEDIA ON YOUTH COGNITIVE DEVELOPMENT - Shoimova Farangiz (TADQIQOTLAR, 2026)
Abstract: In today’s digital era, social media has become an inseparable part of the daily lives of young people all over the world. Rapid technological advancements and the increasing accessibility of the internet have transformed the way youth communicate, learn, and develop cognitively. Millions of young users access social media platforms every minute, seeking information, exchanging ideas, building social connections, and shaping their perceptions about life. With this transformation, significant questions arise: How does the constant exposure to an endless stream of information influence young minds? To what extent does social media usage affect attention span, memory, and critical thinking? This article aims to provide an in-depth analysis on how social media is influencing the cognitive development of young individuals, focusing on both the positive opportunities that are opening up and the concerning challenges that are emerging.